A new cephalopod find in the Eocene beds near Grdoselo in Istria, Croatia - Vasja Mikuž; Miloš Bartol (Geologija, 2012)
The article presents a cast fossil of a cephalopod found in sandy limestones (packstones) of Eocene age nearGrdoselo in Central Istria. The phragmocone remains most probably belong to the nautilid species Eutrephoceras(Simplicioceras) centrale (Sowerby, 1812). We have determined the age of the fossil with calcareous nannoplankton.The nannofossil assemblage is typical of the Middle Eocene and allows the assignment to the biozone NP15(Nannotethrina fulgens) of the Middle Eocene.